Metazoan parasites of blue jack mackerel Trachurus picturatus (Perciformes: Carangidae) from Portuguese mainland waters. Issue 4 (30th June 2015) - Hermida, M.; Pereira, A.; Correia, A.T.; Cruz, C.; Saraiva, A.
Abstract: Blue jack mackerel, Trachurus picturatus, is a carangid fish which constitutes an important commercial resource in the north-east Atlantic. Its metazoan parasite community from Portuguese mainland waters was investigated here for the first time. Nine parasite taxa were found, most of which are common parasites of Trachurus spp. The parasite community was broadly similar to that of the Atlantic horse mackerel, T. trachurus, from the same region, but two digenean species were detected in blue jack mackerel, Monascus filiformis and Tergestia sp., which did not occur in horse mackerel from this region. A comparison with the two previous studies of T. picturatus parasite communities shows that continental-shelf regions are characterized by higher prevalences of digenean trematodes and an absence of trypanorhynch cestodes, in contrast with oceanic regions.